Sites of Japan's Meiji industrial revolution iron and steel, shipbuilding and coal mining, Japan: summary of nomination to the World Heritage list - Kato, Koko 1959- (Department of Industrial Heritage, Cabinet Secretariat, Government of Japan World Heritage Council for the "Sites of Japan's Meiji Industrial Revolution" National Congress of Industrial Heritage, 2013)
This series of industrial heritage sites demonstrates the history of Japan's Meiji Industrial Revolution, which laid the foundation of the Nation of Industry today.